Complex magnetic states in Ni/Fe bi‐segmented nanorods. Issue 12 (6th November 2015) - Mejía‐López, J.; Velásquez, E. A.; López‐Moreno, S.; Mazo‐Zuluaga, J.
Abstract : In this Letter, we discuss the magnetic properties of Ni/Fe bi‐segmented nanorods in a wide range of sizes. We calculated the magnetic phase diagrams, and found new complex magnetic states as well as magnetization reversal schemes which take place depending on the size of the Ni and Fe phases. Differently to the case of systems built by a single component, in the case of these bi‐component systems, due to the interplay among the interchange at interface along with the size and shape effects induced by the dipolar interactions, it is necessary to allow the magnetic relaxation process in order to obtain the magnetic phase diagrams. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The magnetic behavior of Ni/Fe bi‐segmented nanorods of several sizes is investigated by using the Fast Monte Carlo method. The unknown parameter that describes the Fe–Ni interface is computed via density functional theory calculations. With these methods the authors obtain the magnetic phase diagram of the systems in which new complex magnetic states are found. They show that the different states of the phase diagram can be well characterized by the form of the magnetization curves, which can be easily measured in experiments.